Green Synthesis of Silver Nanoparticle Using Usnea cornuta Extract and its Application on Formaldehyde Sensing and Organic Dye Degradation - Lama, Amit; Sapkota, Asmita; Gurung, Bindu; Sinjali, Bishnu Bahadur; Mijar, Krishna; Sharma, Nirmala; Adhikari, Achyut (Journal of Institute of Science and Technology, 2024)
Silver nanoparticles have been widely used in various electronic and sensing devices, coating materials, molecular switches, and data packing. Green synthesis of silver nanoparticles (Ag NPs) has caught much attention in the present world, as it provides an alternative, eco-friendly, and cost-effective process of synthesizing nanoparticles. In this study, Ag NPs were synthesized using Usnea cornuta which was further applied for colorimetric sensing of methylene blue (MB) and formaldehyde in water. UV-visible, FTIR, and XRD techniques were used to characterize the synthesized Ag NPs. The formation of Ag NPs was confirmed by a color change and UV-visible spectroscopy which showed the absorption peak at 417 nm. The face-centered cubic (FCC) structure of a crystal with an average size of 8.3 nm was determined by XRD. The presence of polyphenolic groups as capping agents was confirmed by FTIR spectra. Moreover, the synthesized Ag NPs were able to detect methylene blue and formaldehyde solution even in diluted solution i.e. 1 ppm and 1 %, for MB and formaldehyde respectively. Additionally, the AgNps can degrade methylene blue solution. The degradation efficiency of AgNps was found to be 80% at four hours. The Usnea cornuta shows good potential as a reducing and stabilizing agent, thus it can be utilized for the biosynthesis of silver nanoparticles. The silver nanoparticle can be utilized to sense organic chemical compounds such as methylene blue and formaldehyde in industrial wastewater as well as other wastes. Thus, Ag NPs show good promising colorimetric sensing abilities.